Relationships between morbidity and mortality from Mpox and the human development index (HDI) globally during 2022-2024 epidemics - Prof A Rodríguez-Morales; Dr Jaime A. Cardona-Ospina; Dr D. Katterine Bonilla-Aldana (International Journal of Infectious Diseases, 2025)
Introduction: Multiple aspects of the epidemics of mpox during 2022-2023 have been explored, including clinical features, diagnostic aspects, therapies and vaccines. However, regarding the epidemiological associated factors, socioeconomical aspects have been poorly assessed. Among that, no studies regarding the relationships between the human development index (HDI) and the morbidity and mortality from Mpox have been published yet. Methods: An ecological study for 104 countries was done, using HDI data that were obtained from the United Nations Development Program (UNDP), and the cases, calculating the incidence rates (cases per 100,000 pop.), from the U.S. Centers for Disease Control (CDC) and the World Health Organization (WHO). Also, mortality rates (cases per 100,000 pop.) and case fatality rates (deaths per 100 cases, %CFR), were calculated. The annual variation of the variables was assessed and non-linear regression models (exponential), were done at Stata/MP® v.14.0. Results: At the non-linear regression models, it was observed that the relationship between epidemiological and HDI was significant. During this epidemic higher incidence has been observed in countries with high HDI (r2=0.4132; p<0.0001), however, mortality rates were significantly lower among those countries with higher HDI (r2=0.1317; p=0.0007). Also, the case fatality rate (%CFR) was significantly higher at those countries with lower HDI (r2=0.1595; p=0.0001). Discusion/Conclusions: This information reflect the significant influence of socioeconomical indicators such as the HDI on the Mpox incidence and mortality rates, as well as, on %CFR in the World, particularly in endemic countries. Despite the epidemics of 2022-2024, Mpox continues to be a neglected condition globally, but especially in Africa, where in countries, such as the Democratic Republic of Congo, disease is reemerging again in 2023-2024. More studies on multiple epidemiological factors of Mpox are still to be developed.